Transmission risk evaluation of transfusion blood containing low-density Babesia microti - Cai, Yuchun; Xu, Bin; Liu, Xiufeng; Yang, Wenwu; Mo, Ziran; Zheng, Bin; Chen, Jiaxu; Hu, Wei (Frontiers in Cellular and Infection Microbiology, 2024)
Background Babesia is a unique apicomplexan parasite that specifically invades and proliferates in red blood cells and can be transmitted via blood transfusion, resulting in transfusion-transmitted babesiosis. However, detecting Babesia in blood before transfusion has not received enough attention, and the risk of transfusing blood containing a low density of Babesia microti (B. microti) is unclear, possibly threatening public health and wellness. Purpose This study aimed to determine the lower detection limit of B. microti in blood and to evaluate the transmission risk of blood transfusion containing low-density B. microti. Methods Infected BALB/c mouse models were established by transfusing infected whole blood with different infection rates and densities of B. microti. Microscopic examination, nested Polymerase Chain Reaction (nested PCR), and an enzyme-linked immunosorbent assay (ELISA) were used to evaluate the infection status of the mouse models. Meanwhile, the nested PCR detection limit of B. microti was obtained using pure B. microti DNA samples with serial concentrations and whole blood samples with different densities of B. microti-infected red blood cells. Thereafter, whole mouse blood with a B. microti density lower than that of the nested PCR detection limit and human blood samples infected with B. microti were transfused into healthy mice to assess the transmission risk in mouse models. The infection status of these mice was evaluated through microscopic examination, nested PCR tests, and ELISA. Results The mice inoculated with different densities of B. microti reached the peak infection rate on different days. Overall, the higher the blood B. microti density was, the earlier the peak infection rate was reached. The levels of specific antibodies against B. microti in the blood of the infected mice increased sharply during the first 30 days of infection, reaching a peak level at 60 days post-infection, and maintaining a high level thereafter. The nested PCR detection limits of B. microti DNA and parasite density were 3 fg and 5.48 parasites/μL, respectively. The whole blood containing an extremely low density of B. microti and human blood samples infected with B. microti could infect mice, confirming the transmission risk of transfusing blood with low-density B. microti. Conclusion Whole blood containing extremely low density of B. microti poses a high transmission risk when transfused between mice and mice or human and mice, suggesting that Babesia detection should be considered by governments, hospitals, and disease prevention and control centers as a mandatory test before blood donation or transfusion.